Efficient electrochemical oxygen reduction to hydrogen peroxide by transition metal-doped silicate Sr0.7Na0.3SiO3-delta - Thundiyil, Shibin; Kurungot, Sreekumar; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2021)
Electrochemical oxygen reduction in a selective two-electron pathway is an efficient method for onsite production of H2O2. State of the art noble metal-based catalysts will be prohibitive for widespread applications, and hence earth-abundant oxide-based systems are most desired. Here we report transition metal (Mn, Fe, Ni, Cu)-doped silicates, Sr0.7Na0.3SiO3-delta, as potential electrocatalysts for oxygen reduction to H2O2 in alkaline conditions. These novel compounds are isostructural with the parent Sr0.7Na0.3SiO3-delta and crystallize in monoclinic structure with corner-shared SiO4 groups forming cyclic trimers. The presence of Na stabilizes O vacancies created on doping, and the transition metal ions provide catalytically active sites. Electrochemical parameters estimated from Tafel and Koutechy-Levich plots suggest a two-electron transfer mechanism, indicating peroxide formation. This is confirmed by the rotating ring disc electrode method, and peroxide selectivity and Faradaic efficiency are calculated to be in the range of 65-82% and 50-68%, respectively, in a potential window 0.3 to 0.6 V (vs RHE). Of all the dopants, Ni imparts the maximum selectivity and efficiency as well as highest rate of formation of H2O2 at 1.65 mu mol s(-1).
Keywords: H2O2; mixed metal oxide; ORR; silicate

Effect of B site substitution in Gd2B2-xNiyO7-delta (B= Ti, Zr) ternary metal oxide catalysts in dry reforming of methane - Ghodke, Seema R.; Thundiyil, Shibin; Dongapure, Pavan; Devi, R. Nandini (Molecular Catalysis, 2022)
Structured catalysts are emerging as active and durable catalysts in dry reforming of methane due to their inherent characteristics like lattice insertion of active metals and consequent stability imparted. Here we report Ti and Zr substituted Gd2B2-xNiyO7-delta (B = Ti, Zr) catalysts synthesized by citrate gel method, which are characterized and tested for dry reforming of methane. Structure and Ni substitution has been confirmed by Rietveld refinement of powder XRD patterns and Raman analysis. TPR and CO2-TPD were performed to analyze the reducibility and effect of basic sites of catalysts in DRM activity. Ni doped Ti analogue shows stable and superior activity towards dry reforming of methane for 100 h. The in situ IR studies and XPS analysis confirmed the presence of surface hydroxyl species in this catalyst, which triggers the activation of CO2 and provides higher and durable activity in dry reforming reaction. Absence of any C formation in this catalyst after durability test indicates the mechanism of C gasification by the surface hydroxyl species enhancing stable activity for long durations.
Keywords: A(2)B(2)O(7); Citrate gel method; Dry reforming of methane; Ternary metal oxide